2006
DOI: 10.1093/aje/kwj283
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol Levels and the Risk of Parkinson's Disease

Abstract: Several recent findings suggest a role of lipid and cholesterol metabolism in the pathogenesis of Parkinson's disease. Therefore, the authors examined the association between serum levels of cholesterol and the risk of Parkinson's disease in the prospective, population-based Rotterdam Study among 6,465 subjects aged 55 or more years with repeated in-person examination and on average 9.4 years of follow-up (1990-2004). Higher serum levels of total cholesterol were associated with a significantly decreased risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
132
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(149 citation statements)
references
References 22 publications
13
132
3
1
Order By: Relevance
“…The larger Nurses Health Study and Health Professionals Follow-up Study (in total 530 incident PD cases) found no association between self-reported high cholesterol and PD [634]. However, similar to the Rotterdam study [640], a trend of decreasing PD risk with increasing levels of self-reported total serum cholesterol was observed that was significant in women (p for trend 0.04) but not in men (p for trend 0.19) [634]. In contrast, a…”
Section: Vascular Diseasesmentioning
confidence: 59%
See 2 more Smart Citations
“…The larger Nurses Health Study and Health Professionals Follow-up Study (in total 530 incident PD cases) found no association between self-reported high cholesterol and PD [634]. However, similar to the Rotterdam study [640], a trend of decreasing PD risk with increasing levels of self-reported total serum cholesterol was observed that was significant in women (p for trend 0.04) but not in men (p for trend 0.19) [634]. In contrast, a…”
Section: Vascular Diseasesmentioning
confidence: 59%
“…The Rotterdam study also found that high serum total cholesterol was associated with lower PD risk; the association was, however, observed only in women (RR per mmol increase in cholesterol 0.59, 95% CI 0.45-0.78 in women; 1.01, 95% CI 0.78-1.30 in men) [640]. No association was observed for HDL cholesterol [640]. The larger Nurses Health Study and Health Professionals Follow-up Study (in total 530 incident PD cases) found no association between self-reported high cholesterol and PD [634].…”
Section: Vascular Diseasesmentioning
confidence: 94%
See 1 more Smart Citation
“…Impaired cholesterol homeostasis in serum and brain has been linked to chronic neurodegenerative disorders including Alzheimer's disease, Huntington's disease, Parkinson's disease, Niemann-Pick type C disease and Smith-Lemli Opitz syndrome [9]. There is now emerging evidence indicating that dyslipidaemia is associated with MS disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] Cerebral and serum cholesterol levels follow different metabolic pathways and are only indirectly connected; [34] nevertheless, an inverse correlation between serum cholesterol levels and incidence of Parkinson's disease (PD) was reported in epidemiological studies. [35][36][37] The consumption of polyunsaturated fatty acids (PUFAs) may have protective effects against chronic inflammation [38] and improve cholinergic transmission in the brain. [39] Furthermore, the cerebral levels and chain lengths of PUFAs [40] as well as of sphingolipids [41] play a role in the maintenance of the plasticity of the neuronal network, the derangement of which is closely associated with several neurodegenerative diseases including AD and PD.…”
mentioning
confidence: 99%